Propagation speed of turbulent fronts in pipe flow at high Reynolds numbers. (25th March 2022) - Chen, Kaiwen; Xu, Duo; Song, Baofang
Abstract: Abstract : We investigated the propagation of turbulent fronts in pipe flow at high Reynolds numbers by direct numerical simulation. We used a technique combining a moving frame of reference and an artificial damping to isolate the fronts in short periodic pipes, which enabled us to explore the bulk Reynolds number up to $Re=10^5$ with affordable computation power. We measured the propagation speed of the downstream front and observed that a fit of $1.971-(Re/1925)^{-0.825}$ (in unit of bulk speed) captures this speed above $Re\simeq 5000$ very well. The speed increases monotonically as $Re$ increases, in stark contrast to the decreasing trend above $Re\simeq 10\, 000$ reported by Wygnanski & Champagne ( J. Fluid Mech., vol. 59, 1973, pp. 281–335). The speed of the upstream front overall agrees with the former studies and $0.024+(Re/1936)^{-0.528}$ fits our data well, and those from the literature. Based on our analysis of the front dynamics, we proposed that both front speeds would keep their respective monotonic trends as the Reynolds number increases further. We show that, at high Reynolds numbers, the local transition at the upstream front tip is via high-azimuthal-wavenumber structures in the high-shear region near the pipe wall, whereas at the downstream front tip is via low-azimuthal-wavenumber structures in the low-shear region near the pipe centre. This difference is possibly responsible for the asymmetric speed scalings between the upstream and downstream fronts.